Factors related to hyperuricemia: Filed Survey Examination - Tsuruta, Makoto; Toshima, Hironori; Adachi, Hisashi; Hashimoto, Ryuichi; Tashiro, Hiromi (Journal of the Japanese Association for Cerebro-cardiovascular Disease Control, 1993)
Factors melated to hyperuricemia were examined in Tanushimaru, a farming community. Subjects were 849 males aged 40 to 69 who participated in this field survey in 1989. By multiple logistic regression analyisis, obesity (BMI≥ 25) and the medication with antihypertensive agents were significanty related to hyperuricemia. Obesity showed the highest relative risk, 2.20 (95%C.I. : 1.52-3.20). The positive relation between drinking habits and hyperuicemia has been widely accepted, but from this study that relationship is partially due to the indirect effect of drinking habits with weight gain intervening. High hemoglobin A1c level (HbA1 c > 6.0) did not show a significant relationship to hyperuricemia.